2002
DOI: 10.1002/1616-3028(20021016)12:10<687::aid-adfm687>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Steps During Early Stages of the Aligned Growth of Carbon Nanotubes Using Microwave Plasma Enhanced Chemical Vapor Deposition

Abstract: Vertically aligned carbon nanotubes (CNTs) with controllable length and diameter fabricated by microwave plasma enhanced chemical vapor deposition (MPECVD) are of continuing interest for various applications. This paper describes the role of process gas composition as well as the pre‐coating catalytic layer characteristics. It is observed that nucleation of CNTs was significantly enhanced by adding nitrogen in the MPECVD process, which also promoted formation of bamboo‐like structures. The very first key step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 9 publications
4
33
0
Order By: Relevance
“…tially the vertically oriented N-CNT was synthesized by microwave-plasma enhanced chemical-vapor deposition on a silicon substrate using Fe catalyst. 10 Afterward, the obtained N-CNTs were chlorinated in an inductively plasma coupled reactor at a 5 SCCM ͑SCCM denotes cubic centimeter per minute at STP͒ flow rate of chlorine gas for periods of 5 min. During chlorination the total pressure was 40 mTorr, and the applied input power was 150 W. Oxygen treatment was performed under the air-atmospheric plasma conditions for 5 s at a discharge power of ϳ0.5 kW using a dielectric barrier discharge system.…”
Section: Methodssupporting
confidence: 40%
“…tially the vertically oriented N-CNT was synthesized by microwave-plasma enhanced chemical-vapor deposition on a silicon substrate using Fe catalyst. 10 Afterward, the obtained N-CNTs were chlorinated in an inductively plasma coupled reactor at a 5 SCCM ͑SCCM denotes cubic centimeter per minute at STP͒ flow rate of chlorine gas for periods of 5 min. During chlorination the total pressure was 40 mTorr, and the applied input power was 150 W. Oxygen treatment was performed under the air-atmospheric plasma conditions for 5 s at a discharge power of ϳ0.5 kW using a dielectric barrier discharge system.…”
Section: Methodssupporting
confidence: 40%
“…In addition, it has been found that the nucleation and growth of CNTs may be significantly enhanced by introducing N 2 or NH 3 in the CVD process [6]. Although the mechanism of the enhanced CNT growth in N 2 /NH 3 environment is not yet clear, nitriding the catalyst surface seems to play an important role in CNT growth [7,8]. In this work, we show that aligned CNTs are preferably grown at the grain boundaries of iron nitride (Fe-N) films.…”
supporting
confidence: 42%
“…% wet proofing), and the entire composite was used as the current collector. The detailed procedure for direct growth of CNxNTs can be found elsewhere [23], but is described here briefly. The CNxNTs/CC composite was prepared by nickel-catalyst-assisted MPECVD technique.…”
Section: Preparation Of Cnxnts/cc Current Collectormentioning
confidence: 43%
“…The N 1s XPS spectrum shows two characteristic peaks after N incorporation, compared to that of undoped CNTs, with no evident peaks. The peak located at 398.1 eV is assigned to tetrahedral nitrogen bonding within a substitutional pyridine-like dopant structure, and another peak, located at 400.8 eV, corresponds to trigonal nitrogen bonding within a graphene-like dopant structure [21,23,[28][29][30]. The graphene and pyridine-like defects in the CNxNTs are shown in Figure 5(c).…”
Section: Morphologymentioning
confidence: 45%